Strategic Initiatives for Elevating Muzakki Engagement in Zakat Contributions at Baitul Maal: A Comprehensive Management Approach - Yunus, Ayu Ruqayyah; Putra, Trisno Wardy; Angreni, Rina (Institut Agama Islam Negeri Kendari, 2023)
The main problem in this research is how to optimize efforts to increase awareness of muzakki to pay zakat in Baitul Maal Hidayatullah (BMH) Makassar City. This research uses qualitative research. The data sources in this research are primary data sources and secondary data. The results of research conducted regarding Optimizing Efforts to Increase Awareness of Muzakki issuing zakat at Baitul Maal Hidayatullah Makassar were obtained in order to optimize efforts carried out by implementing management strategies as a form of optimizing long-term and short-term efforts by analyzing opportunities, threats, strengths and weaknesses which are owned. Strategy management goes through three stages, namely formulation, implementation and evaluation. At the formulation stage, the vision mission and objectives of the institution are formulated, which are implemented at the head office. The results of the formulation of the vision and mission are implemented in branch offices throughout Indonesia, including Baitul Maal Hidayatullah Makassar City, Indonesia.